India-Israel Strategic Alliance: Emerging Security Challenges & Policy Options for Pakistan - Nadia Awan; Masood-ur-Rahman Khattak; Amna Mahmood, (ASIAN Journal of International Peace & Security (AJIPS), 2025)
The deepening strategic partnership between India and Israel has reconfigured South Asia’s security environment, with significant implications for Pakistan. Since 1992, expanding cooperation in defense technology, intelligence and cybersecurity largely supported by the United States has enhanced India’s military capabilities and altered regional power asymmetries. This study adopts a qualitative, descriptive and analytical research design and utilizes both primary and secondary sources to examine the evolution and strategic implications of India–Israel relations, with particular emphasis on security cooperation and its regional impact. Drawing on structural realism, this study argues that the India–Israel alignment constitutes a balancing strategy vis-à-vis Pakistan and China, intensifying the regional security dilemma and contributing to strategic instability. Israel’s growing diplomatic support for India on Kashmir further constrains Pakistan’s security and diplomatic space. The paper contends that Pakistan faces declining deterrence credibility and technological marginalization, necessitating adaptive responses through alliance diversification, indigenous defense development and enhanced cyber-security capabilities. Without strategic adjustment, Pakistan’s regional influence is likely to diminish amid the evolving power configuration.